A DFT study of C, SiC, Si, and SiGe colloidal quantum dots for bioimaging - Thirayatorn, Ruhan; Sikam, Pornsawan; Moontragoon, Pairot; Ikonic, Zoran (Asia-Pacific Journal of Science and Technology, 2020)
Photoluminescence of colloidal nanocrystals or quantum dots has great potential in bioanalysis and diagnostic applications, as well as in optoelectronics. In this work C, SiC, Si, and SiGe colloidal quantum dots are formed based on the diamond structure or zinc blende structure with various diameters. Then, an energy-optimized structure was developed, and the electronic structure was investigated using density functional theory (DFT). The absorption coefficient of the energy spectrum of these dots is studied by employing a time-dependent density functional theory (TD-DFT) method. The calculated geometries indicated that these dots are nearly spherical. The electronic structure reveals that the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of energy level can be tuned by changing the quantum dot size, i.e., the energy gaps are reduced when the diameter of these dots is increased. The studied absorption energy reveals that the absorption peak is in the UV-vis range. Moreover, the absorption peak can be engineered, i.e., the absorption wavelength position is blueshifted when the size of the quantum dot is increased, both in the same materials, but in different forms and in the same form of different materials.